2013
DOI: 10.5664/jcsm.2922
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Multiple Sleep Latency Test in Narcolepsy without Cataplexy and Idiopathic Hypersomnia

Abstract: conducted within three weeks of each other.11 Inter-test intervals are generally much longer in clinical practice, and in that case the stability of MSLT features has not been established. We therefore evaluated the test-retest reliability of the MSLT in a clinic population of patients with narcolepsy without cataplexy and idiopathic hypersomnia. METHODS Patient SelectionPatients with a clinical syndrome consistent with a CNS hypersomnia (i.e., reports of problematic, excessive daytime sleepiness persisting ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
107
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 33 publications
(41 reference statements)
4
107
1
1
Order By: Relevance
“…The problems inherent are highlighted by a recent paper assessing the test-retest variability in MSLT findings and diagnosis in adults with hypersomnia. 12 The authors found a change in diagnostic category between cataplexy, idiopathic hypersomnia, and normal occurring in 53% of adults based on MSLT findings. Because of the recent movement towards decriminalization and legalization of marijuana in the USA, with recreational marijuana laws now approved in two states (Colorado and Washington) and medicinal/decriminalized marijuana laws approved in 20 states, 13 awareness of the potential effects of marijuana use on MSLT findings seems important to address, with future studies needed.…”
Section: Resultsmentioning
confidence: 99%
“…The problems inherent are highlighted by a recent paper assessing the test-retest variability in MSLT findings and diagnosis in adults with hypersomnia. 12 The authors found a change in diagnostic category between cataplexy, idiopathic hypersomnia, and normal occurring in 53% of adults based on MSLT findings. Because of the recent movement towards decriminalization and legalization of marijuana in the USA, with recreational marijuana laws now approved in two states (Colorado and Washington) and medicinal/decriminalized marijuana laws approved in 20 states, 13 awareness of the potential effects of marijuana use on MSLT findings seems important to address, with future studies needed.…”
Section: Resultsmentioning
confidence: 99%
“…Still, the diagnostic value of standard MSLT is not optimal as shift work and chronic sleep deprivation can produce similar findings, 5,6 and test-retest reliability of MSLT in hypersomnia conditions is poor. 7 The fact that reported mean sleep latencies in the cohort of Szakacs et al (4.2-4.7 minutes) were somewhat higher than reported in other cohorts including ours (2.6-2.9 minutes), leaves some uncertainty about patient inclusion. 2,8 Even if there remain this and other minor methodological concerns, this study is important and deserves attention by clinicians, politicians, and scientists, and here is why:…”
mentioning
confidence: 57%
“…1 The MSLT as a diagnostic tool in hypersomnias of central origin has been challenged by the presence of SOREMPs in many other conditions (e.g., obstructive sleep apnea); and the poor test-retest reliability of the MSLT. 9 Cataplexy, however, is considered pathognomic of narcolepsy and should be carefully investigated in each patient. The concomitant diagnosis of OSA, narcolepsy, and pseudo-cataplexy in our patient cannot be definitively excluded.…”
Section: Discussionmentioning
confidence: 99%